Analisis Pemilihan Supplier Marmer Dan Granit Menggunakan Metode Analytical Hierarchy Process Pada CV. Unicorn Kencana Indopetra - Sihabbullah, Mukhammad Rayhan; Aslamiyah, Suaibatul (Jurnal Mahasiswa Manajemen, 2024)
Background – CV. Unicorn Kencana Indopetra is a company engaged in the distribution of marble sales. In carrying out its business processes when receiving goods from suppliers, based on pre-research conducted by the author of CV. Unicorn Kencana Indopetra in selecting suppliers using historical data and adjusting according to consumer demand. The selection of suppliers does not use a special method so that sometimes obstacles or problems arise such as goods received are defective, cracked, or broken. This results in quite a lot of losses because the goods purchased do not match the estimated price to be sold due to defects during shipping or not being packed safely from impact. Objective – This study aims to describe the selection of marble and granite suppliers that have been carried out by the company and compare it with the method of selecting marble and granite suppliers using the Analytical Hierarchy Process method. Design / Methodology / Approach – This study uses a qualitative method with a descriptive approach. Data collection techniques used are structured interviews, documentation, focused group discussions. Findings – The results of this study state that the overall AHP Software Expert Choice results, PT. XYZ (Supplier Italia 1) is considered the best supplier with a weight value of 0.327, followed by PT. CDE (Supplier China 1) with a weight value of 0.258, PT. ABC (Supplier Italy 2) with a weight value of 0.187, PT. FGH (Supplier China 2) with a weight value of 0.136, and PT. IJK (Supplier China 3) with a weight value of 0.091. These results indicate that overall, the best suppliers that will be chosen by the company to be used as long-term partners are PT. XYZ (Supplier Italy 1) and PT CDE (Supplier China 1) because overall these suppliers have the highest value compared to the other three suppliers. Research Implication – The findings of this study can be used as a reference if the subsequent research faces conditions similar to the findings in this study. Limitations – This study has limitations in the selection of marble and granite suppliers.